Attitude and Knowledge of Belahi Cattle Rearers for Improve Dairy Farming Practices in Haryana - Ali, Waris; Garai, Sanchita; Maiti, Sanjit; Lepcha, Chimi Yangzom; Meena, Deepak Chand (Indian Journal of Extension Education, 2024)
Belahi cattle are seemed to play an important role in sustaining livelihood security of rural Gujjar pastoralists of the Shivalik foothill of Haryana. So that present study was conducted during June 2019 to March 2021 in selected three districts of Shivalik foothill of Haryana due to native tract of Belahi cattle. From each district one tehsil was selected purposively having the highest Belahi cattle population. Three villages from each Tehsil and twenty migratory Belahi cattle rearer from each village were selected randomly. Therefore, total sample size of the study was 180. Knowledge test and attitude scale developed to ascertain knowledge and attitude of the respondents towards improved dairy farming practices. Belahi cattle rearers possessed medium to higher knowledge and low level of favourable attitude towards scientific dairy farming practices. Majority of the respondents were having good knowledge level about management practices, but very lower level of knowledge about breeding practices. According to the 20th Livestock Census (GOI, 2019), the livestock Livestock sector contribute 4.11 per cent to GDP and 20.5 million people depend upon livestock sector for their livelihood. India is the house of the 536.76 million livestock. Livestock contributed 16 per cent to the income of small farm household as against average of 14 per cent for rural households (20th Livestock Census (GOI, 2019). =Livestock is one of the fast growing sub-sector of agriculture. Millions of rural farmers rely on it for employment and income, and it is also rich source of premium products like milk, meat, and eggs. sector contributes about 26 per cent of total agricultural GDP and also provide employment to approximately 20 million people.
Keywords: Attitude; Belahi; Dairy farming; Knowledge; Livestock